The Role of Organizational Emotions in Strategic Leadership: A literature Review - Sudirman Sudirman (Publikasi Indonesia, 2021)
Emotions are human things. When people consider emotions from a strategic leadership point of view, additional individual framing factors become unavoidable and play a role in an organization's management process. This research aimed to evaluate the existing literature on emotion and strategic leadership comprehensively. The study was a survey of the literature on emotion and strategic leadership. Because of the search and exclusion criteria applied, only 24 articles were relevant. The texts were studied using the grounded theory method to build a new theoretical model and identify essential characteristics of organizational emotion shifting. The model tried to demonstrate how the interaction of human and organizational elements and the task and problems faced by strategic leaders result in internal and external emotional shifts. This literature survey and theoretical integration provided a starting point for further research. The results show that the conceptualization of emotions in strategic leadership encompasses all five levels: positive emotions, negative emotions, emotional empowerment (internal emotion shaping), the establishment of external resources, and the use of power (external emotions shaping). The research revealed that emotion in organizational shaping was a key variable. This variable identified the numerous ways strategic leaders use emotion to shape organizations. It indicates that the concept can bring the person (strategic leader) and organizational levels together. In light of the limited literature, mainly focusing on strategic and emotional leadership, the model should be tested as a foundation for future research.